Implementasi kebijakan manual pendapatan daerah (MAPATDA) di Kotamadya Daerah Tingkat II Ujung Pandang - DACHRI, Ferry (Universitas Gadjah Mada, 1998)
Because of the increasingly scarcity of fund resources for national development we must pay attention and. make an effort in answering the need for financing development, including regional development. All regions in Indonesia are therefore demanded for more efficiently using their financial potential in facing the national financial scarcity. They must use their financial resources in optimally manner in order regional development can be continuously conducted and the result of the development can be evenly distributed in raising people’s well being. The perspective of thinking shows that the regional fund resources management plays an important role in reaching the high level of efficiency and effectively of the allocation of development fund resources. Regional Income Manual Policy (Kebijakan Manual Pendapatan DaeraMMAPATDA) is the system and the procedure of taxation, regional retribution and other regional income. The policy of collecting the Land and Buildings Tax put in effect in all regencies and municipality cities in Indonesia gives the region the direction in effective and efficiently managing the fund resources in conducting governmental and developmental activities. The recent thesis is entitled THE IMPLEMENTATION OF MAPATDA IN SECOND L WEL REGIONAL GOVERNMENT OF UJUNG PANDANG MUNICIPALITY. The thesis is intended to be one of studies investigating how better is the implementation of the MAPATDA by following the existing rules and what factors support and inhibit the implementation of the MAPATDA in the second level regional government of Ujung Pandang municipality. Of the findings resulted and the analysis it is shown that the implementation of the MAPATDA policy in the Ujung Pandang second level regional municipality, is not as optimum as hoped. In other words, the implementation is less effective. It is influenced by the factor of human resources, the factor of organization performance, which are the administrator of MAPATDA, and the factor of organization performance which is the administrator of the MAPATDA, and the factor of MAPATDA control. Related to those matters it is recommended that the function of monitoring in the implementation of the MAPATDA policy must be activated in more effective and efficiently manner. In addition, the organization performance of DIPENDA has also to be raised, as the administrator of MAPATDA, which is now, is still low, along with the increase of the quality of human resources through education and training.